Advances in Corrosion and Protection of Materials (Second Edition) - Renato Altobelli Antunes (Metals, 2025)
As modern civilization, through its extensive use of metallic materials, has given rise to progressively more aggressive environmental conditions, corrosion resistance has become a prominent issue [...]